Des nouveau-nés malformés et un roi boiteux : histoires Spartiates - Jeannine Boëldieu-Trevet (Pallas, 2018)
The study of deformities and disabilities in Sparta immediately raises the issue of sources: there is no appropriate Spartan documentation dealing with this subject. The little insight on this subject comes from an assortment of texts written between the fourth century BC and the rule of the Emperor Adrian. This scarcity makes it difficult to turn malformations and disabilities into subjects of history. Only Plutarch mentioned the fate of the deformed newborns (Life of Lycurgus, 16.1-2). Parallels can however be made with Xenophon, Plato and Aristotle. Concerning adult disabilities, only the case of king Agesilaos has actually been documented. A few questions are addressed here: how did malformed bodies fit into the political, social and cultural construction of Spartan strength and power? Did such perception exist in their statutes? Is there a Spartan specificity?